Different Sequential Chemical Treatments Used to Obtain Bleached Cellulose from Orange Bagasse - Pereira, Paulo Henrique Fernandes [UNESP]; Fernandes, Luana Lima [UNESP]; Santos, Liziane Beatriz Ubirajara [UNESP]; Ornaghi, Heitor L.; Cioffi, Maria Odila Hilário [UNESP] (Taylor & Francis, 2022)
The development of efficient pretreatments is widely used in biobased products aiming to add value to the residue. In this study, orange bagasse is investigated for cellulose extraction under moderate chemical sequential extraction conditions. Three pretreatments are evaluated: alkaline treatment, organosolv, and residue insoluble alcohol. Then, all pretreated samples are bleached. The results are analyzed by chemical composition, Fourier transformed infrared spectroscopy, X-ray diffraction, and thermogravimetric analysis. In general, similar results are observed for all bleaching samples, independently of the pretreatment. A similar cellulose amount is observed among the samples. When compared only to the pretreatments, alkaline shows to be a more effective way of presenting a higher crystallinity index. Hemicellulose and lignin are mostly removed after pretreatment. FTIR and XRD indicated that the pretreatment seems to be more effective in the first step. TG curves presented a more homogeneous pattern due to cellulose removal showing three steps for pre-treatment and two steps for bleached samples. The obtained cellulose has numerous potential applications, and a suitable route can be selected according to available reagents.
Keywords: cellulosic; chemical treatment; green solvents; natural fibers; Orange bagasse; waste bleaching